Identification of Functional Domains in Herpes Simplex Virus 2 Glycoprotein B - Li, Wei (American Society for Microbiology, 2006)
Glycoprotein B (gB) is one of four membrane proteins that are essential for the entry of herpes simplex viruses (HSV) into cells, and coexpression of the same combination of proteins in transfected cells results in cell fusion. The latter effect is reminiscent of the ability of virus infection to cause cell fusion, particularly since the degree of fusion is greatly increased by syncytial mutations in gB. Despite intensive efforts with the gB homologs of HSV and some other herpesviruses, information about functionally important regions in the 700-amino-acid ectodomain of this protein is very limited at present. This is largely due to the misfolding of the majority of the mutants examined. It was shown previously that the percentage of correctly folded mutants could be increased by targeting only predicted loop regions (i.e., not alpha-helix or beta-strand), and by using this approach new functional domains in HSV-2 gB have now been identified.